Observation of new Ξ0c baryons decaying to Λ+c K- - Aaij, Roel; Archilli, Flavio; Bachmann, Sebastian; Berninghoff, Daniel; Borsato, Martino; Dziewiecki, Michal; Gerick, David; Grabowski, Jascha; Günther, Paul André; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; Hu, Jiangqiao; et al. (Physical review letters, 2020)
The Λ+cK− mass spectrum is studied with a data sample of pp collisions at a center-of-mass energy of 13 TeV corresponding to an integrated luminosity of 5.6 fb−1 collected by the LHCb experiment. Three Ξ0c states are observed with a large significance and their masses and natural widths are measured to be m[Ξc(2923)0]=2923.04±0.25±0.20±0.14 MeV, Γ[Ξc(2923)0]=7.1±0.8±1.8 MeV, m[Ξc(2939)0]=2938.55±0.21±0.17±0.14 MeV, Γ[Ξc(2939)0]=10.2±0.8±1.1 MeV, m[Ξc(2965)0]=2964.88±0.26±0.14±0.14 MeV, Γ[Ξc(2965)0]=14.1±0.9±1.3 MeV, where the uncertainties are statistical, systematic, and due to the limited knowledge of the Λ+c mass. The Ξc(2923)0 and Ξc(2939)0 baryons are new states. The Ξc(2965)0 state is in the vicinity of the known Ξc(2970)0 baryon; however, their masses and natural widths differ significantly.